Legal Responsibility of Companies in Implementing Corporate Social Responsibility (CSR) in Indonesia - Lestari Siahaan; Hisar Siregar; Roida Nababan (Journal of Legal and Cultural Analytics, 2025)
Corporate Social Responsibility (CSR) in Indonesia began to develop in the 2000s, along with increasing global awareness of social and environmental issues. The culmination of this development occurred in Indonesia in 2007 with the passing of Law Number 40 on Limited Liability Companies, which requires companies, especially in the natural resource sector, to carry out social and environmental responsibilities. Since then, various regulations and policies have been issued to strengthen CSR obligations, including Law Number 25 of 2007 on Capital Investment and Law Number 32 of 2009 on Environmental Protection and Management. Nonetheless, the implementation of CSR in Indonesia still faces challenges, including violations committed by several companies in Indonesia. This research aims to explore the legal responsibilities of companies in implementing CSR in Indonesia as well as sanctions that can be imposed if companies do not fulfill their obligations. The research method used is normative with qualitative analysis that refers to various laws and regulations and related literature. This research emphasizes the importance of the company's role in sustainable economic development and is oriented towards the welfare of society.